Implementation of Thematic Learning in Islamic Religious Education to Increase the Understanding of Spiritual Values of Elementary School Students - Muhammad Afit Imran; Abdul Halik; Dadang Sumarna (CV. Edujavare Publishing, 2026)
Islamic Religious Education (IRE) in elementary schools is often taught conventionally with an emphasis on memorization, so that students' understanding of spiritual values tends to remain cognitive and has not yet been internalized into daily attitudes. This study aims to analyze the implementation of thematic learning in IRE, identify the spiritual values developed, and reveal its supporting and inhibiting factors at UPT SDN 74 Bolang, Enrekang Regency. The study used a qualitative approach with an intrinsic case study design, conducted from October 2025 to January 2026. Data were collected through observation, in-depth interviews with the principal, the IRE teacher, and homeroom teachers of grades I-VI, and documentation, then analyzed using the Miles and Huberman interactive model (data reduction, data display, and conclusion drawing) and validated through prolonged engagement, persistence of observation, and source triangulation. The results show that thematic learning effectively connects religious teaching with students' real experiences through themes of family, social life, and responsibility, so that the values of honesty, compassion, and responsibility began to appear in students' behavior both at school and at home. Key supporting factors include teacher collaboration, flexible school policy, and parental involvement, while inhibiting factors include limited instructional time, insufficient reinforcement of values at home, and the negative influence of social media. This study contributes a contextual thematic IRE learning model suited to the socio-cultural characteristics of the Enrekang community, serving as a reference for developing similar learning in other elementary schools.